Production of IL-6 and Phagocytosis Are the Most Resilient Immune Functions in Metabolically Compromised Human Monocytes - Krauss, Pierre-Louis; Pfeiffenberger, Moritz; Damerau, Alexandra; Buttgereit, Thomas; Chen, Yuling; Gaber, Timo; Buttgereit, Frank (Frontiers in Immunology, 2021)
At sites of inflammation, monocytes carry out specific immune functions while facing challenging metabolic restrictions. Here, we investigated the potential of human monocytes to adapt to conditions of gradually inhibited oxidative phosphorylation (OXPHOS) under glucose free conditions. We used myxothiazol, an inhibitor of mitochondrial respiration, to adjust two different levels of decreased mitochondrial ATP production. At these levels, and compared to uninhibited OXPHOS, we assessed phagocytosis, production of reactive oxygen species (ROS) through NADPH oxidase (NOX), expression of surface activation markers CD16, CD80, CD11b, HLA-DR, and production of the inflammatory cytokines IL-1β, IL-6 and TNF-α in human monocytes. We found phagocytosis and the production of IL-6 to be least sensitive to metabolic restrictions while surface expression of CD11b, HLA-DR, production of TNF-α, IL-1β and production of ROS through NOX were most compromised by inhibition of OXPHOS in the absence of glucose. Our data demonstrate a short-term hierarchy of immune functions in human monocytes, which represents novel knowledge potentially leading to the development of new therapeutics in monocyte-mediated inflammatory diseases.